2018
DOI: 10.1021/acs.macromol.8b01302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Sequence in Conjugated Triblock Copolymers on Their Aggregation Behavior

Abstract: Conjugated diblock copolymers can exhibit very promising properties, often based on microphase separation. However, both blocks can influence each other's aggregation behavior, which might lead to a suboptimal aggregation behavior of the consecutive blocks. Herein, we investigate whether the introduction of a third, non-aggregating block can render triblock copolymers where the two blocks do not influence the aggregation behavior of one another.Different triblock copolymers consisting of solely thiophene units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…cBCPs with complex architectures have been reported, such as conjugated multi-block copolymers [ 76 , 77 , 78 ], miktoarm star copolymers [ 79 , 80 , 81 , 82 , 83 ], polymer brushes [ 84 , 85 ], dendrimers [ 86 ], cyclic polymers [ 87 ], etc. Similar to binary cBCPs, polymers of other architectures can also be synthesized by using the grafting-from approach and grafting-onto approach.…”
Section: Synthesis Of Conjugated Block Copolymersmentioning
confidence: 99%
“…cBCPs with complex architectures have been reported, such as conjugated multi-block copolymers [ 76 , 77 , 78 ], miktoarm star copolymers [ 79 , 80 , 81 , 82 , 83 ], polymer brushes [ 84 , 85 ], dendrimers [ 86 ], cyclic polymers [ 87 ], etc. Similar to binary cBCPs, polymers of other architectures can also be synthesized by using the grafting-from approach and grafting-onto approach.…”
Section: Synthesis Of Conjugated Block Copolymersmentioning
confidence: 99%
“…From the materials science point of view, triblock copolymers attract significant attention because of their architecture, which enables one to tune the macroscopic properties by changing the position, structure, and length of the third block [ 7 , 8 ]. In contrast to diblock copolymers, in the lamellar phase the triblock macromolecules can be in the looped and bridged configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to well-studied all-conjugated diblock copolymers, the synthesis of all-conjugated triblock copolymers is surprisingly limited due primarily to their relatively difficult synthesis. , An inspiring study has demonstrated to craft all-conjugated thiophene–fluorene–selenophene triblock copolymers by sequential monomer addition using the unassociated catalyst Pd­(Ruphos) . Later, conjugated triblock copolymers consisting of solely thiophene units or containing thiophene and selenophene units demonstrated that when two aggregating blocks are separated by a nonaggregating block because of the large steric hindrance of the side chain, they aggregate separately, while they aggregate as one block when situated next to each other.…”
Section: Introductionmentioning
confidence: 99%